We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
115
1
avatar+983 

Solve the literal equation for x.

 

ax + b + a (x+b) = b

 Nov 19, 2018
edited by Guest  Nov 19, 2018
 #1
avatar+18138 
+1

ax + b + ax + ab = b   subtract b from both sides

2 ax + ab  = 0

2 a x   = -ab

x = -ab/(2a) = - 1/2  b   

 Nov 19, 2018

26 Online Users

avatar
avatar